Perception of principles and values of university social responsibility of the administrative personnel from the Universidad Nacional del Centro del Perú - Huamán Pérez, Francisca (2017)
Different organizations and institutions, especially the private ones, are developing the idea of social responsibility, which is understood as the relationship with their social, environmental and cultural environment. The achievement of university social responsibility demands communication as the primary agent to support participation and generate changes in each of the actors so that they can be cared for, accredited and with full capacity to assume responsibilities. The objective of the research was to know the perception of principles and values of the university social responsibility that the administrators from the Universidad Nacional del Centro del Perú have, it was; guided by a simple descriptive design, with the application of a predesigned survey by Construye País from Chile adapted to reality, coming to at the conclusion that: the practice of the principles and values of university social responsibility related to life in society, according to the administrators ‘perception of the Universidad Nacional del Centro del Perú: manifested in the person´s dignity, freedom, citizenship, participation and democracy, sociability and solidarity, common good and equity, environment and sustainable development, acceptance and appreciation of diversity at a moderate level. This new university social function will allow it to generate positive social impacts, lost since the Peruvian university system came into crisis. Thus, you can find social legitimacy, generating confidence in your students, administrative workers, teachers and the actors of the environment.   DOI: https://doi.org/10.31876/sl.v2i1.3